2010
DOI: 10.1242/jcs.073031
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane domains control exclusion of membrane proteins from clathrin-coated pits

Abstract: SummaryEfficient sorting of proteins is essential to allow transport between intracellular compartments while maintaining their specific composition. During endocytosis, membrane proteins can be concentrated in endocytic vesicles by specific interactions between their cytoplasmic domains and cytosolic coat proteins. It is, however, unclear whether they can be excluded from transport vesicles and what the determinants for this sorting could be. Here, we show that in the absence of cytosolic sorting signals, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
0
26
0
1
Order By: Relevance
“…These puncta co-localized with the late Golgi marker Sec7, but not with the early Golgi marker Rud3, confirming that the protein was accumulating in trans Golgi compartments (Figure 6B and 6C). The same Golgi accumulation of shorter TMDs was observed in cells lacking the End3 protein that is required for endocytosis [40], negating the possibility that the shorter TMD variants are simply travelling to the surface and being more rapidly endocytosed (Figure 6D) [41].…”
Section: Resultsmentioning
confidence: 83%
“…These puncta co-localized with the late Golgi marker Sec7, but not with the early Golgi marker Rud3, confirming that the protein was accumulating in trans Golgi compartments (Figure 6B and 6C). The same Golgi accumulation of shorter TMDs was observed in cells lacking the End3 protein that is required for endocytosis [40], negating the possibility that the shorter TMD variants are simply travelling to the surface and being more rapidly endocytosed (Figure 6D) [41].…”
Section: Resultsmentioning
confidence: 83%
“…The PCR fragment was digested with Hpa I and Kpn I and cloned into prepSC3 (a pDXA-3C plasmid with a modified Hin dIII- Hpa I- Kpn I- Not I- Xba I multiple-cloning site [ Manstein et al , 1995]) digested with Hpa I- Kpn I, creating the csA-0 intermediate construct. The csA-TM construct was obtained by amplifying the sequence coding for the transmembrane domain of CD1b-TM3 (21 aa; Mercanti et al , 2010) and subcloning it in csA-0, using the Kpn I and Xba I sites. The amino acid sequence of the transmembrane domain of csA-TM is: ESD SIVLAIIVPSLLLLLCLALLW YMRRRSM.…”
Section: Methodsmentioning
confidence: 99%
“…In mammalian cells, it has been suggested that exclusion of membrane proteins with long transmembrane domains from clathrin-coated pits explains higher steady state levels at the PM (Mercanti et al, 2010). If the rate of exocytosis is unaffected, it would explain why the proteins yield a higher steady state level at the PM without mediating a more pronounced drag-and-drop missorting of vacuolar cargo.…”
Section: The Ympl Motif Is Dominant and Actively Prevents Ligand Lossmentioning
confidence: 99%